Ni1‐xCoxOy, Ni1‐xCoxSy and Ni1‐xCoxPy Catalysts Prepared from Ni1‐xCox‐ZIF‐67 for Hydrogen Production by Electrolysis in Alkaline Media. Issue 20 (25th September 2019) - Cui, Yuchen; Liu, Zhi; Guo, Hailing; Chai, Yongming; Liu, Chenguang; Mintova, Svetlana
Abstract: The uniform homeotypic bimetallic Ni1‐x Cox Oy, Ni1‐x Cox Sy and Ni1‐x Cox Py catalysts were synthesized from Ni1‐x Cox ‐ZIF‐67 crystals (120‐135 nm) reacting with oxygen, sublimed sulfur and sodium hypophosphite, respectively under control conditions. The catalysts were deposited on glassy carbon electrode (GCE), and their electro‐catalytic activity for hydrogen production in alkaline media by electrolysis was investigated. The electrocatalytic activity of the catalysts towards hydrogen evolution reaction (HER) decreased in the following order Ni0.1 Co0.9 Py >Ni0.2 Co0.8 Oy >Ni0.5 Co0.5 Sy >Ni0.1 Co0.9 ‐ZIF‐67. The Ni0.1 Co0.9 Py exhibited the highest electrocatalytic activity towards HER due to the high crystallinity, high specific surface area and the synergistic effect of nickel and cobalt that accelerate the electron transfer process. Abstract : Ni1‐x Cox Oy, Ni1‐x Cox Sy and Ni1‐x Cox Py catalysts prepared from Ni1‐x Cox ‐ZIF‐67 for hydrogen production by electrolysis in alkaline media. Ni0.1 Co0.9 Py exhibited the highest electrocatalytic activity towards HER due to the high crystallinity, high specific surface area and the synergistic effect of nickel and cobalt that accelerate the electron transfer process.